DIGITAL LITERACY IN ENHANCING ENGLISH LANGUAGE TEACHING EFFECTIVENESS IN UZBEKISTAN - Xudoynazarova Nafisa Xoliqul qizi (TRANSMILLIY QO‘SHMA TA’LIM DASTURLARINING RIVOJLANISHI: O‘ZDJTU TAJRIBASI VA XALQARO SIFAT KAFOLATI TIZIMLARI BO‘YICHA ILMIY-AMALIY YONDASHUVLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
The acceleration of digital transformation in higher education has repositioned digital literacy from a supplementary skill to a structural pedagogical necessity. In Uzbekistan, national educational reforms prioritize digitalization; however, the instructional integration of digital technologies in English Language Teaching (ELT) remains uneven. This study critically synthesizes existing theoretical models of digital literacy and examines their implications for ELT effectiveness in Uzbek higher education. Drawing upon foundational and contemporary scholarship (Gilster, 1997; Reddy et al., 2020; Siregar, 2024; Gruszczynska et al., 2013), the article evaluates the relationship between digital competence, teaching efficiency, learner engagement, and academic mobility. The findings indicate that infrastructural investment alone is insufficient; systemic pedagogical reform and sustained teacher development are required. The study concludes with strategic recommendations aimed at strengthening institutional capacity and ensuring sustainable integration.